Combination of Transverse-Trot Gait Pattern for Quadruped Walking Robot - Yin Tan, Yee; Addie Irawan, Hashim (2015)
This paper presents a combination of transverse and trot walking pattern technique for hexa-quad robot after transformation to optimize the multi-legged robot operation and walking performances. Due to the limitation on the stability of hexapod robot, the combination of hexa-quad walking sequence is proposed to stabilize the quadruped configuration and walking modes. Quadruped robot configuration is stand within dynamically and statically stable criteria if compare to the hexapod robot that has only statically stable criteria. Thus, it is very crucial to have a stable walking sequence technique during walking and operation session. Therefore walking sequence technique to perform for hexa-quad transformation is proposed based on robot’s Center of mass (CoM) and defined support polygon on positioning the leg in transformation process. A real-time based model of hexapod robot control architecture with proposed walking sequence is designed and validated using separated 3 dimensional (3D) simulators. The analysis of robot stepping foot motion is done to verify the desire designed walking sequences and the Body Mass Coordinate (BMC) is analyzed for way point of robot walking.